Effect of bromine-dopant on radiation-driven Rayleigh–Taylor instability in plastic foil. (30th August 2017) - Xu, Binbin; Ma, Yanyun; Yang, Xiaohu; Tang, Wenhui; Ge, Zheyi; Zhao, Yuan; Ke, Yanzhao; Kawata, Shiego
Abstract: Effects of bromine (Br) dopant on the growth of radiation-driven ablative Rayleigh–Taylor instability (RTI) in plastic foils are studied by radiation hydrodynamics simulations and theoretical analysis. It is found that the Br-dopant in plastic foil reduces the seed of ablative RTI. The main reasons of the reduction are attributed to the smaller oscillation amplitude of ablative Richtmyer–Meshkov instability (RMI) induced by the smaller post-shock sound speed, and the smaller oscillation frequency of ablative RMI induced by the smaller ablation velocity and blow-off plasma velocity. The Br-dopant also decreases the linear growth rate of ablative RTI due to the smaller acceleration. Treating the perturbation growth as a function of foil's displacement, the perturbation growth would increase in Br-doped foil at the phase of ablative RTI, which is attributed to the decrease of the ablation velocity and the density gradient scale length. The results are helpful for further understanding the influence of high- Z dopant on the radiation-driven ablative RTI.